Initial boiling temperature research in the closed diphasic thermosiphon - Кравец, Владимир Юрьевич; Чернобай, Вадим Алексеевич; Никитенко, Анна Анатолиевна; Голамреза, Бехмард (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents results of the research of the initial boiling in the heating area of the closed two-phase thermosyphon are offered. It is shown, that the initial boiling temperature depends on the type of the heat transfer agent and geometrical features of the thermosyphon